The Effect of Hypertension Exercise on Blood Pressure Reduction in The Elderly at Wisma Seruni UPT PSTW Jember - Riski Hidayaturrohkim; Echi Agnes Claudia; Yuzqi Rizqullah; Dimas Anggi Septiyansah; Nanda Leoni Agustin; Fahruddin Kurdi; Septin Wahyu Ersanti (Nusantara Scientific Medical, 2023)
As the elderly population increases and the aging process they experience, triggers the occurrence of various diseases, especially hypertension. Improper management of hypertension causes a decrease in quality of life and morbidity in the elderly. This study aims to determine the effect of hypertension exercise on the blood pressure of the elderly at Wisma Seruni UPT PSTW Jember. The design of this study used a quasi-experimental with pretest and posttest one group design. The sampling technique used was a total of 8 respondents who met the inclusion criteria. Changes in blood pressure were measured using an aneroid sphygmomanometer and data analysis using the statistical test T-Test Dependent. The results showed that the average systolic blood pressure (SBP) before the first day of therapy was 147.5 mmHg and the second day 138.75 mmHg while the average systolic blood pressure after the elderly hypertension exercise was carried out on the first day of 140 mmHg and the second day 131.25 mmHg, the average diastolic blood pressure (DBP) before the first and second day of therapy was 84.38 mmHg while after the first day of therapy it was 82.5 mmHg and the second day was 80.63 mmHg. Based on the results of the analysis test using the dependent t-test, the SBP results before and after the intervention were 0.000 (p<0.005). There was an effect on the decrease in systolic blood pressure on the first and second day of intervention. Hypertension exercise therapy is an alternative solution to reduce blood pressure in the elderly with hypertension.